Nonclinical Evaluation of PF-06438179: A Potential Biosimilar to Remicade® (Infliximab). Issue 11 (November 2016) - Derzi, Mazin; Johnson, Theodore; Shoieb, Ahmed; Conlon, Hugh; Sharpe, Penny; Saati, Andrew; Koob, Sarah; Bolt, Michael; Lorello, Leslie; McNally, Jim; Kirchhoff, Carol; Smolarek, Teresa; et al.
Abstract Introduction PF-06438179, a potential biosimilar to Remicade® (infliximab, Janssen Biotech, Inc.), is a chimeric mouse–human monoclonal antibody targeting human tumor necrosis factor alpha (TNF). Methods Analytical (small subset reported here) and nonclinical studies compared the structural, functional, and in vivo nonclinical similarity of PF-06438179 with Remicade sourced from the United States (infliximab-US) and/or European Union (infliximab-EU). Results The peptide map profiles were superimposable, and peptide masses were the same, indicating identical amino acid sequences. Data on post-translational modifications, biochemical properties, and biological function provided strong support for analytical similarity. Administration of a single intravenous (IV) dose (10 or 50 mg/kg) of PF-06438179 or infliximab-EU to male rats was well tolerated. There were no test article-related clinical signs or effects on body weight or food consumption. Systemic exposures [maximum drug concentration (C max ) and area under the concentration–time curve (AUC)] in rats administered PF-06438179 or infliximab-EU were similar, with mean exposure ratio of PF-06438179 relative to infliximab-EU ranging from 0.88 to 1.16. No rats developed anti-drug antibodies. A 2-week IV toxicity study was conducted with once-weekly administration of 10 or 50 mg/kg of PF-06438179 to male and female rats. PF-06438179-related hyperplasia of sinusoidal cells occurred in the liver in rats administered 50 mg/kg, but was not adverse based on its minimal to mild severity. The no-observed adverse-effect level for PF-06438179 was 50 mg/kg. At this dose, C max was 1360 µg/mL and AUC at 168 h was 115, 000 µg h/mL on day 8. Conclusions The analytical and nonclinical studies have supported advancement of PF-06438179 into global comparative clinical trials. Funding Pfizer Inc.